2016
DOI: 10.11648/j.ijema.20160406.13
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Implications of Flaring and Venting in Crude Oil and Natural Gas Production

Abstract: It is believed that production of crude oil and natural gas without flaring and venting is neither technically nor economically feasible. In the face of this challenge, it is pertinent to understand the technical, economic, environmental, and social effects of flaring and venting in the production of crude oil and natural gas. This paper is a review of the role of flaring and venting in the production of oil and gas and an exposition of the environmental consequences of flaring and venting with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Much of the available literature focuses on the environmental impacts; however, Okoye et al 24 argue that one of the biggest effects of gas flaring's adverse effects on the environment is the enormous waste of money required to clean up the environment, pay for medical care, and ultimately lose human capital. Ngene et al 25 reviewed the role of flaring and venting in the production of oil and gas, while Mansoor and Tahir 26 reviewed current gas flaring reduction and utilization techniques for the production of energy-efficient fuels. Importantly, Mansoor and Tahir 26 conclude that an opportunity to be exploited in the use of gas flare is a future clean energy economy, as methane has already shown in the production of energy with the abatement of CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the available literature focuses on the environmental impacts; however, Okoye et al 24 argue that one of the biggest effects of gas flaring's adverse effects on the environment is the enormous waste of money required to clean up the environment, pay for medical care, and ultimately lose human capital. Ngene et al 25 reviewed the role of flaring and venting in the production of oil and gas, while Mansoor and Tahir 26 reviewed current gas flaring reduction and utilization techniques for the production of energy-efficient fuels. Importantly, Mansoor and Tahir 26 conclude that an opportunity to be exploited in the use of gas flare is a future clean energy economy, as methane has already shown in the production of energy with the abatement of CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the EPA's assessment (2016) found that there were no widespread or systemic impacts of hydraulic fracturing on drinking water. In addition, oil and gas drilling often includes a "flaring" process that releases toxic pollutants like sulfur dioxide into the air, a greenhouse gas that can both accelerate climate change and cause acid rain (Ngene et al, 2016). While natural gas is an attractive alternative to coal because it releases about half as many greenhouse gas emissions (Lomborg, 2012), the release of methane from hydraulic fracturing into the atmosphere still generates greenhouse gasses that can accelerate climate change (Meng & Ashby, 2014).…”
Section: The Benefits and Negative Consequences Of Hydraulic Fracturingmentioning
confidence: 99%
“…The main aring products are greenhouse gases and black carbon (BC) [5,6]. Flaring gas negatively affects human health, causing cancer, lung damage, neurological and skin problems, reproductive and blood issues, emphysema, bronchitis, respiratory irritation, asthma, shortness of breath, mortalities, and developmental effects [7][8][9]. Sulfur dioxide (SO 2 ) and nitrogen oxides (NOx) are considered to be the primary sources of acid rain when they react with atmospheric moisture to form sulfuric and nitric acids.…”
Section: Introductionmentioning
confidence: 99%